A conceptual approach for aircraft readiness management through aircraft downtime optimisation. (24th January 2022) - Makrygianni, Maria; Tsarouhas, Panagiotis
A framework for aircraft downtime optimisation in a military squadron was proposed. Military squadron was considered as a production system, producing operational aircraft. Each working day that an aircraft is out of service is a defective product. A group of 30 aircraft was studied in order to determine the proportion of defectives. Laney P ′ chart depicted that the aircraft maintenance performance was in control. Nevertheless, two aircraft had undergone to unusual downtime interval. For these aircraft, cannibalisation, waiting and repairing time was analysed with partial least square regression. Eight points came up as outliers and leverages. The analysis of these points revealed that airframe powerplant general (APG), communication/navigation, electrical and structure systems have undergone long waiting and repairing time, while recovery of fuel and electrical systems is downgraded by cannibalisation time. Incorporation of this methodology in aviation would strengthen the optimisation process of readiness, maintenance costs, quality, and safety.